2017
DOI: 10.1002/cphc.201601417
|View full text |Cite
|
Sign up to set email alerts
|

SILAR BiOI‐Sensitized TiO2 Films for Visible‐Light Photocatalytic Degradation of Rhodamine B and 4‐Chlorophenol

Abstract: BiOI nanoplates were deposited upon a film of TiO nanoparticles derived from a commercial source using a simple room temperature sequential ionic layer adsorption and reaction (SILAR) method. X-ray diffraction, X-ray photoelectron spectroscopy and electron microscopies have been used to confirm the crystal phase, chemical states of key elements and morphology of the BiOI nanoplate-TiO composites. Using both valence band X-ray photoelectron spectroscopy and UV/Vis diffuse reflectance measurements the band struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 54 publications
(99 reference statements)
3
17
0
Order By: Relevance
“…Upon thermal treatment under N 2 the films were found to turn from the characteristic yellow colour of the surface complex to a light brown, indicating the decomposition of the organic catechol to carbon. The general synthetic procedure is given in Figure , in which the initial TiO 2 film is formed by a doctor blading method (see the Experimental Section) giving a film, which has previously been found to be 10–12 microns thick . Hydrolysis of TiCl 4 to give TiO 2 is typically followed up with a thermal treatment step in air to give complete conversion to crystalline TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Upon thermal treatment under N 2 the films were found to turn from the characteristic yellow colour of the surface complex to a light brown, indicating the decomposition of the organic catechol to carbon. The general synthetic procedure is given in Figure , in which the initial TiO 2 film is formed by a doctor blading method (see the Experimental Section) giving a film, which has previously been found to be 10–12 microns thick . Hydrolysis of TiCl 4 to give TiO 2 is typically followed up with a thermal treatment step in air to give complete conversion to crystalline TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The kinetics of photocatalytic degradation of organic pollutants and dyes by semiconductors have been most often treated as first order kinetics. This is most common in literature, and as an example one of the recent references [15,54,55 and many other references] is provided. In Table.4.…”
Section: Kinetics Of Photodegradation Of Dyesmentioning
confidence: 96%
“…The majority of the studies reported in literature deal with the effect on degradation activity on variables like the amount of the catalyst, the concentration of the dye employed, pH, effect of the radiation source and time of irradiation and also the effect of dissolved oxygen and others. The kinetics of degradation of dyes on most of the catalyst systems studied follows first order [15].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we have developed successful photocatalysts based on TiO 2 , including C-TiCl 4 -TiO 2 , 21 BiVO 4 -TiO 2 , 22 BiOI-TiO 2 23 and Bi 4 Ti 3 O 12 -TiO 2 . 24,25 These offer enhanced photocatalytic activity over un-modified titania and, thus far, the most promising of these under laboratory conditions is the Bi 4 Ti 3 O 12 -TiO 2 co-catalyst system (BTO-TiO 2 ), attributed to its good stability and the presence of the heterojunction band architecture, which can reduce the extent of charge recombination.…”
Section: Environmental Science: Water Research and Technology Papermentioning
confidence: 99%